Different readings of Olfa Edilbi’s "Damascus: The Smile of Sadness" : A female perspective - القصيري, نضال (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This paper attempts to approach the different readings of Olfa Edilbi’s Damascus: The Smile of Sadness from a female perspective, through delving into four readings, which are: the readings of female critics (Eman Alqadhi, Sahar Shbeeb, Buthaina Sha’aban and Majida Hammoud, respectively). The paper aims at sketching the major points of these readings in the light of the Reception Theory, which originated from the German Constance School and crystalized at the hands of Hans Robert Jauss and Wolfgang Iser. This is done through the answers the novel provides to the female critics’ questions he development of such answers through history, and identification of the textual structures they addressed. They intended to fill in the gaps through the interaction between these textual structures and their expectations. The paper concludes that the female question constitutes the major part of the female critics’ readings of the novel and a woman’s freedom lies in her self-reliance, her non-surrender to her feminine condition, and the necessity of arming her with education and knowledge, in addition to the need for political issues to coincide with issues of women’s liberation. Artistically speaking, the craftsmanship of Olfa Edlibi measured to the critics’ horizon of expectations.